Genome-wide identification, evolution and expression profiles analysis of bHLH gene family in Castanea mollissima - Yu, Liyang; Fei, Cao; Wang, Dongsheng; Huang, Ruimin; Xuan, Wang; Guo, Chunlei; Jing, Liu; Meng, Wang; Yi, Lu; Zhang, Haie; Zhang, Jingzheng (Frontiers in Genetics, 2023)
Abstract The basic helix-loop-helix (bHLH) transcription factors (TFs) gene family is an important gene family in plants, and participate in regulation of plant apical meristem growth, metabolic regulation and stress resistance. However, its characteristics and potential functions have not been studied in chestnut (Castanea mollissima), an important nut with high ecological and economic value. Here, 94 CmbHLHs were identified in chestnut genome, of which 88 were unevenly distributed on chromosomes, and other six were located to five unanchored scaffolds. Almost all CmbHLH proteins were predicted in the nucleus, and subcellular localization demonstrated the correctness of the above predictions. Based on the phylogenetic analysis, all of the CmbHLH genes were divided into 19 subgroups with distinct features. Abundant of cis-acting regulatory elements related to endosperm expression, meristem expression, gibberellin (GA) and auxin responses were identified in the upstream sequences of the CmbHLH genes, indicated that they may play potential functions in morphogenesis of chestnut. Comparative genome analysis showed that dispersed duplication was the main driving force for the expansion of the CmbHLH genes, which was experienced purifying selection pressure during evolution. Transcriptome analysis and qRT-PCR experiments showed that the expression patterns of CmbHLHs were different in different chestnut tissues, and revealed some members may play potential functions in chestnut buds, nuts, fertile/abortive ovules development. This comprehensive analysis will be helpful to understand the characteristics and potential functions of the bHLH gene family in chestnut.